Development of benzimidazole-based derivatives as antimicrobial agents and their synergistic effect with colistin against gram-negative bacteria - Dokla, Eman M. E.; Abutaleb, Nader S.; Milik, Sandra N.; Li, Daoyi; El-Baz, Karim; Shalaby, Menna-Allah W.; Al-Karaki, Rawan; Nasr, Maha; Klein, Christian D.; Abouzid, Khaled A. M.; Seleem, Mohamed N. (European journal of medicinal chemistry, 2020)
Gram-negative bacteria pose a distinctive risk worldwide, especially with the evolution of major resistance to carbapenems, fluoroquinolones and colistin. Therefore, development of new antibacterial agents to target Gram-negative infections is of utmost importance. Using phenotypic screening, we synthesized and tested thirty-one benzimidazole derivatives against E. coli JW55031 (TolC mutant strain). Compound 6c showed potent activity with MIC value of 2μg/ml, however, it lacked activity against several Gram-negative microbes with intact efflux systems, including E. coli BW25113 (wild-type strain). Combination of 6c with colistin partially restored its antibacterial activity against wild strains (MIC range, 8-16μg/ml against E. coli, K. pneumoniae, A. baumannii, and P. aeruginosa). 6c exhibited no cytotoxicity against two mammalian cell lines. Therefore, compound 6c represents a promising lead for further optimization to overcome Gram-negative resistance alone or in combination therapy.